Diet constraints of indigenous children in conflict and non-conflict areas of Davao del Norte, Philippines - Ricalde, Ruby Grace J. (2018)
Indigenous People (IP) have poorer nutritional status compared to non-IPs due to their remote and upland location, high poverty incidence, and occurence of armed conflict, which limit their access to stable and nutritious food.
Keywords: Indigenous children -- Nutritional aspects